2016
DOI: 10.1080/02699931.2015.1129314
|View full text |Cite|
|
Sign up to set email alerts
|

What's so funny? Modelling incongruity in humour production

Abstract: Finding something humorous is intrinsically rewarding and may facilitate emotion regulation, but what creates humour has been underexplored. The present experimental study examined humour generated under controlled conditions with varying social, affective, and cognitive factors. Participants listed five ways in which a set of concept pairs (e.g. MONEY and CHOCOLATE) were similar or different in either a funny way (intentional humour elicitation) or a "catchy" way (incidental humour elicitation). Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…With reference to the former, in particular, this change in interpretation is the result of the resolution of the incongruity. It has also been demonstrated that this pattern elicits pleasurable emotions in those who are telling the joke (Hull et al, 2016 ).…”
Section: Placing the Pleasure Elicited By Humor And Insight Problem Smentioning
confidence: 97%
“…With reference to the former, in particular, this change in interpretation is the result of the resolution of the incongruity. It has also been demonstrated that this pattern elicits pleasurable emotions in those who are telling the joke (Hull et al, 2016 ).…”
Section: Placing the Pleasure Elicited By Humor And Insight Problem Smentioning
confidence: 97%
“…Furthermore, the use of particular obscenity helps to heighten the experience, perspective, and effect of the speaker. There is a quite interesting study in terms of the humour production conducted by Hull, Tosun, & Vaid (2017). This study came up with the statement that surprisingness is the crucial notion in producing humour.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Specifically, the incongruity theory holds that the perception of incongruity leads to humour when two normally disparate concepts, schemata, or meanings are juxtaposed in a surprising or unexpected manner (Attardo & Raskin 1991;Coulson 2001;Ruch 2008). It has received considerable empirical support (Deckers & Buttram 1990;Hull et al 2017;etc.). Suls (1972: 85-89) streamlines the humour appreciation process in a three-stage information processing model: a setup stage where a prediction is made for comparison with the most recent text input, an incongruity stage where the input does not match the prediction, and a resolution stage where one engages in figuring out how the punchline is congruent with the preceding text.…”
Section: When the Incongruity Theory Of Humour Meets Prototype Theorymentioning
confidence: 99%